Asymptomatic Bacteriuria among Pregnant Women Attending Antenatal Care at Hiwot Fana Specialized University Hospital, Harar, Eastern Ethiopia: Magnitude, Associated Factors, and Antimicrobial Susceptibility Pattern - Mekuria Edae; Zelalem Teklemariam; Fitsum Weldegebreal; Degu Abate (International Journal of Microbiology)
Background. Asymptomatic bacteriuria is one of the major risk factors for the development of urinary tract infections during pregnancy which accounts for about 70% of the cases. However, there is no guideline which recommends routine screening of pregnant women for asymptomatic bacteriuria in most of developing countries including Ethiopia. Thus, the aim of this study was to determine the magnitude, associated factors, and antimicrobial susceptibility pattern of asymptomatic bacteriuria among pregnant women. Methods. A cross-sectional study was conducted from March to April 2019. Data were collected through face-to-face interview and analyzed using Statistical Package for Social Science version 22. A test of association was performed using logistic regression and P value less than 0.05 was considered statistically significant. Results. The overall prevalence of asymptomatic bacteriuria was 19.9%. Direction of wiping after genital wash, postcoital urination, and catheterization were factors significantly associated with asymptomatic bacteriuria. Most of the isolated Gram positive were highly sensitive to Ceftriaxone (90.9%). Coagulase-negative staphylococci showed higher sensitivity to Augmentin (75.0) and Ceftriaxone (87.5%), whereas they showed resistance to Clindamycin (68.7%) and Ampicillin (62.5%). Gram-negative bacteria isolates showed higher sensitivity to Ceftriaxone (88.2%), Gentamycin (67.5%), and Augmentin (64.7%), while they showed resistance to Ampicillin (70.5%) and Clindamycin (50.0%). Conclusion. The overall prevalence of asymptomatic bacteriuria among pregnant women in this study was high. Direction of wiping after genital wash, catheterization, and postcoital urination increases the odds of asymptomatic bacteriuria. Therefore, health education on the predisposing factors is strongly recommended.